2013
DOI: 10.1038/bjc.2013.670
|View full text |Cite
|
Sign up to set email alerts
|

ING4 regulates JWA in angiogenesis and their prognostic value in melanoma patients

Abstract: Background:We previously showed that inhibitor of growth family member 4 (ING4) inhibits melanoma angiogenesis, and JWA suppresses the metastasis of melanoma cells. As angiogenesis is essential for tumour metastasis, further investigation of the function of ING4 and JWA in melanoma angiogenesis is needed, and their prognostic value are of great interest.Methods:Western blot, tube-formation assays and luciferase assays were used to investigate the correlation between ING4 and JWA in melanoma angiogenesis. JWA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…Hou et al also found that ING4 could act as an E3 ubiquitin ligase to induce ubiquitination and degradation of p65, which is an additional mechanism to link ING4 to NF-κB [80]. In addition, ING4 was the upstream regulator of JWA, activating JWA promoter, inhibiting ILK and downstream NF-κB/IL-6/STAT3/VEGF signaling pathways, thus promoting melanoma angiogenesis [81]. In melanoma, ING4 was induced by BRMS1 (Breast cancer metastasis suppressor 1), a metastasis suppressor, and regulated angiogenesis through inhibiting NF-κB activity and IL-6 level [82].…”
Section: Angiogenesismentioning
confidence: 97%
“…Hou et al also found that ING4 could act as an E3 ubiquitin ligase to induce ubiquitination and degradation of p65, which is an additional mechanism to link ING4 to NF-κB [80]. In addition, ING4 was the upstream regulator of JWA, activating JWA promoter, inhibiting ILK and downstream NF-κB/IL-6/STAT3/VEGF signaling pathways, thus promoting melanoma angiogenesis [81]. In melanoma, ING4 was induced by BRMS1 (Breast cancer metastasis suppressor 1), a metastasis suppressor, and regulated angiogenesis through inhibiting NF-κB activity and IL-6 level [82].…”
Section: Angiogenesismentioning
confidence: 97%
“…The selection of melanoma tissue blocks and construction of tumor tissue microarrays have been described previously [6,7,12,[33][34][35][36][37]. The formalinfixed, paraffin embedded archival biopsies of benign melanocytic nevi, melanoma in situ, invasive primary melanoma and metastatic melanoma were obtained from the 1990 to 2009 archives from the Department of Pathology at Vancouver General Hospital, Vancouver, Canada.…”
Section: Immunohistochemistry (Ihc) Staining Of Tissue Microarraysmentioning
confidence: 99%
“…The clinicopathological data was available for all melanoma cases. EYA1 expression was analyzed by immunohistochemistry on paraffin-embedded tissue microarrays as described previously [6,7,12,[33][34][35][36][37]. Briefly, de-paraffinized 4μm tissue sections were treated 30 minutes in 0.1M sodium citrate (PH6.0) at 95˚C for antigen retrieval.…”
Section: Immunohistochemistry (Ihc) Staining Of Tissue Microarraysmentioning
confidence: 99%
See 2 more Smart Citations